E-stability and stability of adaptive learning in models of asymetric information - Maik Heinemann (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2007)
The paper demonstrates how the Estability principle introduced by Evans and Honkapohja can be applied to models with heterogeneous and private information in order to assess the stability of rational expectations equilibria under learning. The paper extends already known stability results for the Grossman and Stiglitz model to a more general case with many differentially informed agents and to the case where information is endogenously acquired by optimizing agents. In both cases it turns out that the rational expectations equilibrium of the model is inherently E-stable and thus locally stable under recursive least squares learning.
Keywords: D31; E62; O41; P16; 330